2017
DOI: 10.1080/13549839.2016.1274721
|View full text |Cite
|
Sign up to set email alerts
|

Food justice youth development: using Photovoice to study urban school food systems

Abstract: ABSTRACT:How do youth learn through participation in efforts to study and change the school food system? Through our participatory youth action research (YPAR) project, we move beyond the "youth as consumer" frame to a food justice youth development approach. We track how a group of youth learned about food and the public policy process through their efforts to transform their own school food systems by conducting a participatory evaluation of farm-to-school efforts in collaboration with university and communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 35 publications
(17 reference statements)
0
30
0
Order By: Relevance
“…Ten studies revealed programs focused on supporting critical consciousness development through out-of-school programs. These programs often utilized yPAR (Foster-Fishman et al, 2010; Groves Price & Mencke, 2013; Harper et al, 2017; Rodríguez, 2008; Sánchez Carmen et al, 2015) or service learning (Winans-Solis, 2014) activities that were designed specifically to promote critical reflection and critical action among youth. One study (Sánchez Carmen et al, 2015) detailed the use of a yPAR approach and an ethnic studies curriculum to support critical consciousness development.…”
Section: What Interventions Have Been Used To Foster Critical Conscio...mentioning
confidence: 99%
“…Ten studies revealed programs focused on supporting critical consciousness development through out-of-school programs. These programs often utilized yPAR (Foster-Fishman et al, 2010; Groves Price & Mencke, 2013; Harper et al, 2017; Rodríguez, 2008; Sánchez Carmen et al, 2015) or service learning (Winans-Solis, 2014) activities that were designed specifically to promote critical reflection and critical action among youth. One study (Sánchez Carmen et al, 2015) detailed the use of a yPAR approach and an ethnic studies curriculum to support critical consciousness development.…”
Section: What Interventions Have Been Used To Foster Critical Conscio...mentioning
confidence: 99%
“…Photovoice, a YPAR approach, consists of involving people in the process of taking photographs to document social issues that are of concern to them (Wang, 2006). Youth have used photovoice to document public health concerns (Necheles et al, 2007), violence (Chonody et al, 2013), schools, and educational inequality (Harper et al, 2017) among many other social concerns. The program used a photovoice methodology given its ability to help young people generate policy solutions and actively participate in their community (Wang, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While urban agriculture in general has received increased attention from scholars (Grewal and Grewal, 2012; McPherson, 2011; Mendes et al , 2008; Mougeot, 2006; Summer et al ., 2010; Surls et al , 2014), over the past several decades, youth urban agriculture has likewise received considerable attention (Fifolt et al. , 2018; Harper et al , 2017; Pudup, 2008; Russ and Gaus, 2021, Sutton, 2007; Weissman, 2014). Urban agriculture has embraced youth education for multiple reasons, given that it serves as a “multifunctional activity” (Russ and Gaus, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%